Simulation of Tilapia Cultivation Using The Monte Carlo Method (Suggested Simulation for Abdul Hadi Fish Cultivation) - Mad Yusup; Muhammad Hardianto; Hurun’in (STIE AAS Surakarta, 2021)
Fish consumption in Indonesia has increased in the last 5 years. Tilapia includes five types of fish that account for more than 80% of the total production. This shows that the cultivation of tilapia using pond ponds also has a great opportunity to become a business. By simulating the cultivation of tilapia first before the cultivation process is carried out, the research costs become cheaper because there is no need to carry out an experimental cultivation process that costs money to buy broodstock and cultivation equipment. Monte Carlo was chosen as the simulation method because Monte Carlo Simulation is a method for evaluating a deterministic model involving random numbers as one of the inputs. The results showed that the number of tilapia harvests at the end of cultivation carried out in 6 months was 802 and the profit that could be obtained at the end of cultivation was Rp. 37,554,274.00.